2022
DOI: 10.1371/journal.pone.0279075
|View full text |Cite
|
Sign up to set email alerts
|

Impact role stress on turnover intentions of Pakistan’s healthcare workers: Mediating and moderating role of organizational cynicism and self-efficacy

Abstract: Nurses make up most of the global healthcare system, thus justifying their significance in the respective industry. The healthcare profession is amongst the very few careers that are attributed to a very high level of stress and imbalanced work-life equilibrium. Over past decades, the said nature of work has been observed to coerce countless nurses to leave their respective organizations. Considering this, the current study primarily evaluates the impact of role stressors on the turnover intentions of nurses e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 116 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…For instance, Mochamad Soelton et al ( 1 ) analyzed the factors affecting the turnover intention of waiters in chain restaurants. Tahira Nazir et al ( 2 ) studied the moderating and mediating role of organizational cynicism and self-efficacy in the relationship between work stress and turnover intention of medical workers in Pakistan. Lijin Shao et al ( 3 )used the JDCS model to study the relationship between psychological contract, work stress, and turnover intention of employees in information service companies.…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
“…For instance, Mochamad Soelton et al ( 1 ) analyzed the factors affecting the turnover intention of waiters in chain restaurants. Tahira Nazir et al ( 2 ) studied the moderating and mediating role of organizational cynicism and self-efficacy in the relationship between work stress and turnover intention of medical workers in Pakistan. Lijin Shao et al ( 3 )used the JDCS model to study the relationship between psychological contract, work stress, and turnover intention of employees in information service companies.…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
“…High stress is one of the important causes of turnover intention in the healthcare staff, such as overload [ 6 ], repellent communication [ 7 ], the risk of exposure to infectious diseases [ 8 ], work-family conflict and role ambiguity [ 9 ]. The survey has shown that 2.2% to 14.5% of female healthcare staff feel great pressure [ 10 ].…”
Section: Introductionmentioning
confidence: 99%